Bortezomib, lenalidomide and dexamethasone (VRd) vs carfilzomib, lenalidomide and dexamethasone (KRd) as induction therapy in newly diagnosed multiple myeloma - Tan, Carlyn Rose; Derkach, Andriy; Nemirovsky, David; Ciardiello, Amanda; Diamond, Benjamin; Hultcrantz, Malin; Hassoun, Hani; Mailankody, Sham; Shah, Urvi; Maclachlan, Kylee; Patel, Dhwani; Lahoud, Oscar B.; et al. (Blood cancer journal (New York), 2023)
Lenalidomide and dexamethasone with bortezomib (VRd) or carfilzomib (KRd) are commonly used induction regimens in the U.S. This single-center, retrospective study evaluated outcomes and safety of VRd and KRd. Primary endpoint was progression-free survival (PFS). Of 389 patients with newly diagnosed multiple myeloma, 198 received VRd and 191 received KRd. Median PFS was not reached (NR) in both groups; 5-year PFS was 56% (95%CI, 48–64%) for VRd and 67% (60–75%) for KRd ( P = 0.027). Estimated 5-year EFS was 34% (95%CI, 27–42%) for VRd and 52% (45–60%) for KRd ( P < 0.001) with corresponding 5-year OS of 80% (95%CI, 75–87%) and 90% (85–95%), respectively ( P = 0.053). For standard-risk patients, 5-year PFS was 68% (95%CI, 60–78%) for VRd and 75% (65–85%) for KRd ( P = 0.20) with 5-year OS of 87% (95%CI, 81–94%) and 93% (87–99%), respectively ( P = 0.13). For high-risk patients, median PFS was 41 months (95%CI, 32.8–61.1) for VRd and 70.9 months (58.2-NR) for KRd ( P = 0.016). Respective 5-year PFS and OS were 35% (95%CI, 24–51%) and 69% (58–82%) for VRd and 58% (47–71%) and 88% (80–97%, P = 0.044) for KRd. Overall, KRd resulted in improved PFS and EFS with a trend toward improved OS compared to VRd with associations primarily driven by improvements in outcome for high-risk patients.